Kinerja Pelayanan Bidang Rehabilitas Sosial Dinas Sosial Kota Palangka Raya (Studi Kasus Pengemis): Service Performance in the Social Rehabilitation Sector of the Palangka Raya City Social Service (Case Study of Beggars) - Pahlawan, Reza; Prasetiawan, Kristian Lutpian (Pencerah Publik, 2017)
This study aims to describe and describe the Service Performance of the Social Rehabilitation Sector of the City of Palangka Raya Social Service (a case study of Beggars). The research method used is a qualitative description which is where the researcher wants to describe and describe the Service Performance of the Social Rehabilitation Sector of the City of Palangka Raya Social Service (a case study of Beggars). Sources of data namely in this study are primary data and secondary data which is the primary data source is the General and Personnel Subdivision, SUB Division of Social Rehabilitation Services. Data collection techniques in this study are Observation, Interview, and Documentation. Based on the research results that the Service Performance of the Social Rehabilitation Sector of the City of Palangka Raya Social Service (Case Study of Beggars) is not good enough because it can be seen from the absence of concrete data between the number of beggars who enter and leave every day/month, lack of government funds to handle these beggars the lack of infrastructure that supports beggar rehabilitation and service programs such as the unavailability of shelters for beggars in rehabilitation, which makes many beggars still exist.